Risk Factors Associated With Early-Onset Esophageal Cancer in Tanzania. (3rd February 2022) - Buckle, Geoffrey C.; Mmbaga, Elia J.; Paciorek, Alan; Akoko, Larry; Deardorff, Katrina; Mgisha, William; Mushi, Beatrice P.; Mwaiselage, Julius; Hiatt, Robert A.; Zhang, Li; Van Loon, Katherine
Abstract : PURPOSE: Eastern Africa is one of several regions affected by high incidence rates of esophageal squamous cell carcinoma (ESCC). A unique epidemiologic feature of ESCC in Eastern Africa is the high incidence in young people, with one-third of cases diagnosed at age < 45 years. This study aimed to investigate risk factors for early-onset ESCC in Tanzania through a secondary analysis of a matched case-control study. MATERIALS AND METHODS: From 2013 to 2015, ESCC cases were recruited at Muhimbili National Hospital and Ocean Road Cancer Institute in Dar es Salaam, Tanzania. Hospital controls were identified from patients with nonmalignant conditions and matched 1:1 for sex and age (± 10 years). Questionnaires were used to assess sociodemographic characteristics and environmental, dietary, and lifestyle risk exposures. Multivariate logistic regression models were used to estimate age-specific odds ratios of ESCC for exposures among participants age 30-44 and ≥ 45 years. RESULTS: A total of 471 cases and 471 controls were enrolled. Among cases, 100 (21%) were < 45 years. Multiple exposures were identified as risk factors for early-onset ESCC, several of which were unique to this age group, including infrequent teeth cleaning, secondhand tobacco smoke exposure, and pest infestation of grain and/or nuts. Lower socioeconomic status, family history of ESCC, tobacco smoking, home-brewed alcohol consumption, home storage of grain and/or nuts, and use of firewood for cooking were associated in the older but not the younger age group. Hot beverage intake was associated with increased ESCC risk in both age groups. CONCLUSION: Our results suggest that ESCC risk factors in Tanzania vary between age groups. With the data currently available, environmental and behavioral risk factors appear to play an important role in the high incidence of ESCC among young people. Abstract :